Penerapan Model Discovery Learning untuk Meningkatan Kemampuan Berpikir Kritis Siswa - Nurlaili Handayani; Basariah Basariah; Sawaludin Sawaludin (Jurnal Pendidikan Indonesia, 2022)
skills at SMPN 10 Mataram class 8-J Civics learning is the goal of this research with the type of classroom action research in two cycles. Each cycle in this research consists of 4 (four) stages, namely (1) planning stage; (2) implementation stage; (3) the observation stage; and (4) the reflection stage. The results showed that the first cycle of data, the number of indicators for the action variable, namely the Discovery Learning , was 37 descriptors that appeared as many as 29 descriptors. The percentage of the emergence of critical thinking skills which is the variable of hope is 22 people (68.7%) from 32 people. Based on the data from the first cycle, which shows that the performance indicators of the expectation variable and the action variable have not been achieved, a reflection is carried out to examine the achievement of the predetermined performance indicators. From this reflection, the input in the form of learning devices was improved so that in the second cycle the quality of the learning process also increased by 37 descriptors (100%). The increase in the quality of the action variable was also followed by an increase in the expectation variable, namely students' critical thinking to 26 students (81.2%). From the results of this study, it was stated that the application of the discovery learning in Civics learning was able to improve the critical thinking skills of 8-J grade students of SMPN 10 Mataram.